0937 The Evaluation of Brain Maturation by REM Sleep Analyses During Puberty Using Fast Fourier Transform. (27th May 2020) - Lopes, M; Roizenblatt, S
Abstract: Introduction: Brain maturation has been associated with electroencephalogram (EEG) changes during rapid eye movement (REM) sleep. There is a higher delta power during sleep in the first decade of the human EEG and this fact might be related to puberty period. Most studies assessed EEG during wakefulness and NREM sleep. The aim of this study was to evaluate changes in the REM sleep EEG spectral analysis across puberty. Methods: Twenty healthy children were studied. They were divided into two groups: early puberty (n=10, ageranging from 6 to 12) and late puberty (n=10, age= ranging from 13 to 18). Polysomnography was performed in 2 nights, one for adaptation purpose. The Tanner scales were obtained and exclusion criteria were the presence of sleep and daytime complaints at least 14 days before recruitment. Fast Fourier Transform (FFT) was performed in C3-A2 derivation throughout all night. The FFT was calculated in 4s windows and the mean of delta (0.5-2.0 Hz), delta 2 (2.0-4.0 Hz), theta (4.0-8.0 Hz), alpha (8.0 - 12.0 Hz), sigma (12.0-16.0 Hz) and beta (16.0 - 20.0 Hz) were obtained. Results: We found differences during NREM and REM sleep between two groups (U-test, p<0.05). In REM sleep, the delta 2 (U-test, p=0.02)and theta power were higher in early puberty group (U-test p=0.04). The delta power correlated negatively with the duration in minutes of stage 1 (rs =-0.46 p<0.05), and the wake time after sleep onset (rs =-0.48, p<0.05) and correlated positively with sleep efficiency (rs =0.45, p<0.05). Theta power during REM sleep also correlated positively with N3 sleep stage (rs =0.45, p<0.05). Conclusion: The REM sleep can be an extremely useful biomarker of brain function for future therapeutic protocols. The present results suggest that there are changes in REM sleep EEG throughout puberty, and that they may be related to puberty brain maturation. The hormone therapy may have an action in the REM behavioral Sleep Disorder. Future studies are need to evaluate this hypothesis. Support: N/A